UPAYA PENINGKATAN MINAT BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH MENGGUNAKAN PENDEKATAN BERDIFERENSIASI KELAS XI SMAN N 12 PEKANBARU - Winda Febiola Samosir; Suroyo; Adiva Septiara; Rizka Septiani Aulia; Sessy Masesa (STKIP Subang, 2025)
This research is motivated by History learning in class XI 9 of SMA Negeri 12 Pekanbaru which still uses conventional learning centered on the teacher. This results in low student interest in learning History. Evidenced by the results of the questionnaire which showed a percentage value of 12.2% and included in the criteria of